Randomized clinical trial on the preservation of the medial pectoral nerve following mastectomy due to breast cancer: impact on upper limb rehabilitation - Gonçalves, Andrea de Vasconcelos; Teixeira, Luiz Carlos; Torresan, Renato; Alvarenga, César; Cabello, César (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Systematic modifications to the surgical technique of mastectomy have been proposed with the objective of minimizing injuries to the pectoral nerves and their effects. The aim of this study was to compare muscle strength and mass of the pectoralis major muscle (PMM) and abduction and flexion of the homolateral upper limb following mastectomy among women with breast cancer undergoing either preservation or sectioning of the medial pectoral nerve (MPN). DESIGN AND SETTING: Randomized, double-blind, clinical trial on 30 women with breast cancer who underwent mastectomy between July 2002 and May 2003 in Campinas, Brazil. METHODS: The women were allocated to a group, in which the MPN was preserved, or to another group in which it was sectioned. Fisher’s exact and Wilcoxon tests were used to analyze the data, along with Friedman and ANOVA analysis of variance. RESULTS: In the MPN preserved group, 81% of the women did not lose any PMM strength, compared with 31% in the sectioned MPN group (confidence interval, CI = 1.21; relative risk, RR = 2.14; P < 0.03). There were no differences between the groups regarding muscle mass (CI = 0.32; RR = 0.89; P = 0.8), shoulder abduction (CI = 1.36; RR = 0.89; P = 0.28) and shoulder flexion (CI = 1.36; RR = 1.93; P = 0.8). CONCLUSIONS: Preservation of the MPN was significantly associated with maintenance of PMM strength, compared with nerve sectioning. No differences in muscle mass or in abduction and flexion of the homolateral shoulder were found between the groups. CLINICAL TRIAL REGISTRATION NUMBER: ANZCTR - 00082622